Contributions to the Development of Tetrahedral Mobile Robots with Omnidirectional Locomotion Units - Anca-Corina Simerean; Mihai Olimpiu Tătar (Machines)
In this paper, the authors present the process of modeling, building, and testing two prototypes of tetrahedral robots with omnidirectional locomotion units. The paper begins with a detailed description of the first tetrahedral robot prototype, highlighting its strengths as well as the limitations that led to the need for improvements. The robot’s omnidirectional movement allowed it to move in all directions, but certain challenges related to stability and adaptability were identified. The second prototype is presented as an advanced and improved version of the first model, integrating significant modifications in both the structural design and the robot’s functionality. The authors emphasize how these optimizations were achieved, detailing the solutions adopted and their impact on the robot’s overall performance. This paper includes an in-depth comparative analysis between the two prototypes. The analysis highlights the considerable advantages of the second prototype, demonstrating its superiority. The conclusions of the paper summarize the main findings of the research and emphasize the significant progress made from the first to the second prototype. Finally, future research directions are discussed, which include refining control algorithms, miniaturizing the robot, improving structural performance by integrating shock-absorbing dampers, and integrating lighting systems and video cameras.